PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 29 PADANG - Syahputri, Nivo Prima; Mukhni, Mukhni; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
Â This research did based on the studentsâ problem at grade VII SMPN 29 padang in learning mathemathics which make the students get overwhelmed in finishing the task if the teacher give different exercise with the example given by the student.The type of this research is experimental research in which the research subjects are chosen randomly. The sampling methods did randomly. There are two classes that become tha sample they are VII7 as exerimental class and VII6 as control class.The instrument used by the researche is quiz and mathematics concept comprehension test by using essay formÂ with the reablility test is .the data analysis that is used is one side t test. Based on the result of data analysis it is known that both of sample classes is normal and homogen distribution in the real degree Î± = 0,05. the result of hypothesis testing got from P-value = 0,001 is lower than Î± = 0,05, therefore the hypothesis, in this research, is accepted